Spatiotemporally Controlled Reorganization of Signaling Complexes in the Plasma Membrane of Living Cells. Issue 44 (30th September 2015) - Wedeking, Tim; Löchte, Sara; Birkholz, Oliver; Wallenstein, Alexander; Trahe, Julia; Klingauf, Jürgen; Piehler, Jacob; You, Changjiang
Abstract : Triggered immobilization of proteins in the plasma membrane of living cells into functional micropatterns is established by using an adaptor protein, which is comprised of an antiGFP nanobody fused to the HaloTag protein. Efficient in situ reorganization of the type I interferon receptor subunits as well as intact, fully functional signaling complexes in living cells are achieved by this method.